The Effect of Digital Marketing on Purchase Decisions Through Purchase Intention as an Intervening Variable at The Cafe Kopi Kenangan in Samarinda - Habibah, Ummu; Istimaroh, Istimaroh (Research in Management of Technology and Business, 2024)
This study aims to determine the effect of Digital Marketing on Purchasing Decisions through Buying Intention as an intervening variable at Café Kopi Kenangan Samarinda. Through Buying Intention as an intervening variable at Café Kopi Kenangan Samarinda. Population in the study This study is a consumer who has purchased a product at Café Kopi Kenangan Coffee. This research uses descriptive quantitative type. The sample used in this study amounted to 213 respondents which were taken using the probability sampling method using simple random sampling. The data collection technique was carried out using a questionnaire in the form of a Google Form link. Data processing method The data processing method used in this study was IBM SPSS software and SmartPLS software. The results showed that digital marketing has a positive and significant effect on purchasing decisions, digital marketing has a positive and significant impact on purchase intentions, and digital marketing has a positive and significant effect on purchase intentions. Has a positive and significant impact on purchase intention, purchase intention has a positive and significant effect on purchasing decisions, digital marketing has a positive and significant impact on purchasing decisions through purchase intention as an intervening variable. Purchase decision through purchase intention as an intervening variable.